Designing a High‐Performance Lithium–Sulfur Batteries Based on Layered Double Hydroxides–Carbon Nanotubes Composite Cathode and a Dual‐Functional Graphene–Polypropylene–Al2O3 Separator. (23rd November 2017) - Hwang, Jang‐Yeon; Kim, Hee Min; Shin, Subeom; Sun, Yang‐Kook
Abstract: Designing an optimum cell configuration that can deliver high capacity, fast charge–discharge capability, and good cycle retention is imperative for developing a high‐performance lithium–sulfur battery. Herein, a novel lithium–sulfur cell design is proposed, which consists of sulfur and magnesium–aluminum‐layered double hydroxides (MgAl‐LDH)–carbon nanotubes (CNTs) composite cathode with a modified polymer separator produced by dual side coating approaches (one side: graphene and the other side: aluminum oxides). The composite cathode functions as a combined electrocatalyst and polysulfide scavenger, greatly improving the reaction kinetics and stabilizing the Coulombic efficiency upon cycling. The modified separator enhances further Li + ‐ion or electron transport and prevents undesirable contact between the cathode and dendritic lithium on the anode. The proposed lithium–sulfur cell fabricated with the as‐prepared composite cathode and modified separator exhibits a high initial discharge capacity of 1375 mA h g −1 at 0.1 C rate, excellent cycling stability during 200 cycles at 1 C rate, and superior rate capability up to 5 C rate, even with high sulfur loading of 4.0 mg cm −2 . In addition, the findings that found in postmortem chracterization of cathode, separator, and Li metal anode from cycled cell help in identifying the reason for its subsequent degradation upon cycling in Li–S cells. Abstract : The enhanced lithium–sulfur cell design including a MgAl‐LDH@CNT‐S composite cathode and a DF‐GPA separator is proposed. By improving lithium–sulfur redox reactions and minimizing the risk of internal short circuit, this cell configuration enables to yield superior rate capability up to 5 C rate and excellent long‐term cycling stability even with high sulfur loading in the electrode of 4.0 mg cm −2 .